The Relationship between Fibromyalgia and Pressure Pain Threshold in Patients with Dyspareunia - Hasan Terzi; Rabia Terzi; Ahmet Kale (Pain Research and Management)
OBJECTIVE: To evaluate the number of tender points, pressure pain threshold and presence of fibromyalgia among women with or without dyspareunia.